Adolescent externalizing behaviour, psychological control, and peer rejection: Transactional links and dopaminergic moderation. (24th March 2017) - Janssens, Annelies; Van Den Noortgate, Wim; Goossens, Luc; Verschueren, Karine; Colpin, Hilde; Claes, Stephan; Van Heel, Martijn; Van Leeuwen, Karla
Abstract : This study investigated (1) reciprocal links among parental psychological control, peer rejection, and adolescent externalizing (aggressive and rule‐breaking behaviour), and (2) the moderating effect of an adolescent genetic factor (biologically informed polygenic score for dopamine signalling). Three‐year longitudinal data from 1, 116 adolescents (51% boys; M age = 13.79) and their parents included psychological measures (adolescent‐reported psychological control, peer‐reported rejection, and parent‐reported aggressive and rule‐breaking behaviour). Cross‐lagged analyses showed bidirectional effects between psychological control and both aggressive and rule‐breaking behaviour and a unidirectional effect of peer rejection on both forms of problem behaviour over time. Multigroup structural equation modelling revealed genetic moderation only for rule‐breaking behaviour: for adolescents with intermediate levels of dopamine signalling significant environmental effects were present, whereas adolescent effects of rule‐breaking behaviour on psychological control were significant for adolescents with both intermediate and high profiles and effects on peer rejection only for adolescents with high dopamine profiles. Statement of contribution What is already known on this subject? Parental psychological control is related to adolescent externalizing problems. Experiencing peer rejection reinforces aggressive and rule‐breaking behaviour. Single‐gene studies show that dopaminergic genes influence externalizing problems directly or in interaction with the environment. What does this study add? Parental psychological control and adolescent aggressive and rule‐breaking behaviour exacerbate one another longitudinally. Longitudinal associations between peer rejection and both subtypes of externalizing behaviour are unidirectional. With a polygenic approach, dopaminergic moderation is present for rule‐breaking behaviour only.